Investigaion of SBR/CMC blends by vulcanizing and swelling properties - Krmelová, Vladimíra; Krmela, Jan (Univerzita Pardubice, 2012)
Blends of Styrene butadiene rubber (SBR) with varying loading degree from 10 wt% to 100 wt% of carboxymethylcellulose (CMC) have been prepared. The prepared SBR/CMC blends were submitted to measurements of vulcanizing characteristics (MH, ML, ts, tc(90), Rv) as a function of loading degree of CMC. Swelling has been used in the study of elastomeric networks. Swelling equilibrium data, for a new SBR/CMC rubber vulcanizates in xylen, were analyzed by the Flory-Rehner equation simply to obtain a measure of the crosslink density. Results obtained showed that 10 wt% of CMC in blends has comparable properties with standard.
Keywords: styrene butadiene rubber; carboxymethylcellulose; vulcanization; crosslink density